Anosmia as a clinical predictor to non-fatal COVID-19 case and better survivability (Research, Society and Development, 2022)
Recently, a respiratory infectious disease labeled as COVID-19 caused by SARS-CoV-2 had taken over the world by storm. This RNA virus can cause various symptoms such as malaise, anosmia, ageusia, fever, cough, headache, myalgia, diarrhea, and ARDS. COVID-19 patients have specific symptoms such as fever. In another study, it was said that anosmia could be a benchmark for screening for COVID-19. in a study of young patients and was more common in women. The average onset of anosmia occurs on day 4 after infection and lasts for 8 days. the evidence says that this disease can cause a decrease in a person's quality of life. The exact cause of anosmia is still unknown, but several theories suggest that anosmia can occur due to damage to nerve receptors, inflammation of olfactory epithelial cells, and dysfunction of nerve receptors. The popular theory is that anosmia occurs due to inflammation of the olfactory epithelial cells, thereby damaging the olfactory receptors. The inflammation blocks odors from reaching the nasal mucosa and can inhibit receptor excitability and signal transduction. Anosmia may be associated with lower hospital mortality rates. However, further research and discovery is needed to fully grasp the pathophysiological concept of COVID-19 induced anosmia. This review will discuss the pathophysiology and review the lower anosmia mortality rate. This article reviews current understandings about the pathophysiology of anosmia and its potential as a marker towards better clinical prognosis. This narrative review aims to provide knowledge about updates regarding the pathophysiology of anosmia as a clinical predictor of mild and severe COVID-19 symptoms.